Human immunodeficiency virus ocular involvement and retinopathy: Clinical spectrum and management strategies - Hou-Ting Kuo; Hsin Tseng; Alan Y. Hsu; Bing-Qi Wu; Ning-Yi Hsia; Chun-Ju Lin; John Gonzales (Taiwan Journal of Ophthalmology)
This study highlights the significant ocular complications associated with human immunodeficiency virus (HIV), particularly its impact on the retina. Historically, HIV infection frequently resulted in severe retinal infections, such as Cytomegalovirus retinitis. However, with the widespread adoption of highly active antiretroviral therapy, the prevalence of these infections has significantly declined. Despite this progress, unresolved challenges in treatment approaches remain. In addition, HIV is known to cause nonopportunistic ocular conditions, such as optic neuropathy, immune recovery uveitis, and HIV-associated retinopathy, which require further clinical attention. In addition, we conducted an in-depth discussion on the phenomenon of early senescence in HIV patients. With the widespread adoption of optical coherence tomography angiography, this technology has enabled us to detect subtle changes associated with early senescence at an earlier stage. In this review, we conducted an extensive literature search to consolidate current evidence on the ophthalmic manifestations of HIV, particularly among patients in Taiwan. By synthesizing this information, we aim to highlight areas for improvement in clinical practice and offer insights into optimizing care for HIV patients with ocular complications.